EFL STUDENTS' PERCEPTIONS TOWARD VOCABULARY LEARNING BY LISTENING TO ENGLISH SONGS ON SPOTIFY - Epril L. Butar Butar; Caroline V. Katemba (UIBU, 2023)
This research aimed to discover the differences in attitudes, personal feelings, and perceptions of English as a Foreign Language (EFL) students from secondary and tertiary levels toward vocabulary learning by listening to English songs on Spotify. The researcher conducted the study using a descriptive quantitative research design and distributed a questionnaire to 97 EFL students via Google Forms to collect data. Those EFL students were 45.4% tertiary students (44 people) and 54.6% secondary students (53 people) from various schools and colleges who were listening to an English song on Spotify and taking English classes. According to the research, EFL students largely agreed and expressed positive attitudes, personal feelings, and perspectives toward vocabulary learning by listening to English songs on Spotify. They also believed that doing so helped them learn vocabulary because of the Spotify’s advantages, which include being a great resource for learning vocabulary from sources like English song lyrics. The researcher also hopes that this study will aid students in learning vocabulary and that other researchers working on related topics will find it useful as a resource. Teachers may use Spotify as a teaching tool when teaching vocabulary.